Simultaneous Determination Of Atenolol And Hydrocholrothiazide In Tablets Formulation By Derivative Spectrometry (JOURNAL OF ADVANCES IN CHEMISTRY, 2020)
The derivative spectrophotometric method was developed and applied for the simultaneous determination of Atenolol (ATE) and Hydrochlorothiazide (HCT) in Tablets formulations. The first derivative spectrophotometric (1DS) method was applied for the determination of (ATE) and (HCT), respectively. (ATE) was determined at 271.9 nm (1D 271.9) and (HCT) was determined at 279.3 nm (1D 279.3). Linearity showed a good correlation coefficients R2 = 0.9994 and R2 = 0.9989 for (ATE) and (HCT), respectively. Linearity ranges were (10 – 280)